Sustav skrbi za branitelje iz Domovinskog rata - Dobrotić, Ivana (Array, 2008)
In the introductory part of the paper, the author considers the challenges of the process of reintegration of war veterans into peacetime and civilian life. The author emphasises that the key prerequisite for a successful reintegration is the improvement of the employment level of the veteran population. The consequences of the Homeland War, and the characteristics of the aid programme for war veterans in Croatia and in other countries are briefl y outlined. The paper provides a comprehensive overview of the rights of the Homeland War veterans and their family members, and the data on the number of users and the expenses for certain rights in the period from 2002 until 2006. The defenders make a relatively numerous groups in the overall Croatian population, even in comparison to the military powers such as the USA. Comparatively viewed, the Republic of Croatia intended a wide sphere of rights for its defenders, and these rights range over almost all social security systems, but they stretch even beyond that. The data show that there is a constant growth in the number of the users of certain rights, but also of the expenses related to that. A large and constant growth of the users of the right of the disability allowance and a large number of unemployed defenders are particularly worrying. Despite large expenses for the housing allocation, numerous requests remain unsolved, and will represent a problem that the governments will have to deal with for a long time. Finally, the author warns about the lack of evaluation of the existing aid programmes, as well as on the need to redirect the welfare systems for the defenders from mainly compensatory measures to the development of various integration programs